Experiences of children who have gone through the foster care program in Zimbabwe. - Konzo, Brian (Midlands State University, 2017)
The research examined the experiences of children who have gone through the foster care program in Zimbabwe. Children coming into foster care would have been take away from their parents may be facing emotional, psychological and behavioural problems due to the turmoil, abuse and negligence they may have experienced as such it is critical to emphasise the healing aspect of foster care. There are certain challenges from the system which need to be addressed. This research was guided by three research questions, how foster care positively impacted the lives of children in Zimbabwe, the major challenges faced by children who go through foster care and central issues in foster care which children want to be addressed. In order to understand the experiences of children in foster care, a case study which is an explorative design was used. Data was collected using the purposive sampling targeting 24 foster children, 6 registered foster parents and 2 probation officers, all participants being from Harare province. In-depth interviews were conducted. The study established that foster children experience improved lifestyle during placements, having the opportunity to be part of a family, have access to better education and being part of an open society where they can create lifelong relationships. Foster care system has challenges which include failure by the children to adjust to the home environment, lack of basic needs and lack of government support. Conclusively, the research discovered that more needs to be done to improve the foster care. The research recommended increased public awareness to provoke and attract new candidates for foster parents in the country, provision of support from the government to the foster parents in form of grants, health and educational assistance.